IMPROVING ORGANIZATIONAL PERFORMANCE WITH ORGANIZATIONAL CULTURE AND TRANSFORMATIONAL LEADERSHIP THROUGH INTERVENING ORGANIZATIONAL COMMITMENT VARIABLES - Rahmatullah, Asep; David Ramdansyah, Agus; Kambara, Roni; Haryadi, Didit (Dinasti International Journal of Digital Business Management, 2022)
This study aims to examine and analyze the influence of organizational culture and transformational leadership on organizational performance through organizational commitment. This study uses a descriptive quantitative method with a causal approach. The object of this research is the regeneration of the Indonesian Democratic Party of Banten Province using a sample of 158 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. Data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Organizational culture has a positive and significant effect on organizational performance. 2). Transformational leadership has a positive and significant effect on organizational performance. 3). Organizational culture has a positive and significant effect on organizational commitment. 4). Transformational leadership has a positive and significant effect on organizational commitment. 5). Organizational commitment has a positive and significant effect on organizational performance. Organizational commitment can mediate between organizational culture and transformational leadership in partial mediation.